Antiviral treatment for outpatient use during an influenza pandemic: a decision tree model of outcomes averted and cost-effectiveness - Venkatesan, Sudhir; Carias, Cristina; Biggerstaff, Matthew; Campbell, Angela P; Nguyen-Van-Tam, Jonathan S.; Kahn, Emily; Myles, Puja R.; Meltzer, Martin I (Oxford University Press, 2019)
Background: Many countries have acquired antiviral stockpiles for pandemic influenza mitigation and a significant part of the stockpile may be focussed towards community-based treatment.